2008
DOI: 10.1186/bf03352872
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater level changes related to the ground shaking of the Noto Hanto Earthquake in 2007

Abstract: The Geological Survey of Japan, AIST has been monitoring groundwater using the observation network of about 40 stations in and around the Kinki and Tokai districts for earthquake prediction research. The Noto Hanto Earthquake in 2007 (M JMA 6.9) occurred in the northwestern part of the Noto Hanto Peninsula, Japan on March 25, 2007. The epicentral distance to the nearest and furthest observation well is about 100 km and 400 km, respectively. Changes in groundwater level related to the Noto Hanto Earthquake were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Dynamic strain, induced by the passage of seismic waves, can also cause groundwater‐level changes (Montgomery & Manga ; Itaba et al . ). Several studies have investigated the relationship between co‐seismic water‐level changes and ground shaking in Taiwan and Japan (Wang et al .…”
Section: Mechanisms Of the Co‐seismic Water‐level Changementioning
confidence: 97%
See 1 more Smart Citation
“…Dynamic strain, induced by the passage of seismic waves, can also cause groundwater‐level changes (Montgomery & Manga ; Itaba et al . ). Several studies have investigated the relationship between co‐seismic water‐level changes and ground shaking in Taiwan and Japan (Wang et al .…”
Section: Mechanisms Of the Co‐seismic Water‐level Changementioning
confidence: 97%
“…; Wong & Wang ; Itaba et al . ). As the peak ground velocity ( PGV ) is proportional to the dynamic strain (Brodsky et al .…”
Section: Mechanisms Of the Co‐seismic Water‐level Changementioning
confidence: 97%
“…Modeling of volumetric strain due to fault movement during earthquakes has been conducted in previous studies Rojstaczer et al 1995;Koizumi et al 1996;Quilty and Roeloffs 1997;Grecksch et al 1999;Lee et al 2002;Matsumoto et al 2003;Koizumi et al 2004;Itaba et al 2008;Shi et al 2014;Cucci and Tertulliani 2015). The polarities of some calculated strains are moderately consistent with the observed changes; however, the magnitude of most calculated strains did not match the observed changes Grecksch et al 1999;Matsumoto et al 2003;Koizumi et al 2004;Itaba et al 2008;Shi et al 2014). Long-term data of groundwater level in the near-field revealed that only co-seismic falls were recorded at LJ3 and 11 out of 13 changes were co-seismic rises at PD.…”
Section: Discussionmentioning
confidence: 72%
“…Since then, digital and automatic instrumental records of water level changes during earthquakes have become available, and significant achievements have been obtained in terms of quantitative analyses (Cooper et al 1965;Roeloffs 1998;Wang and Manga 2010). With an abundance of observational data, the co-and post-seismic changes in the water levels of wells have been reported and are among the most widely documented earthquake-induced hydrologic phenomena (Wang and Manga 2010); for example, the changes in groundwater and the mechanisms associated with earthquakes have been studied in the U.S. (Rojstaczer and Wolf 1992;Peltzer et al 1996), Japan (Wakita 1975;Akita and Matsumoto 2004;Itaba et al 2008), India (Ramana et al 2007;Radhakrishnan et al 2010), Europe (Grecksch et al 1999), and China (Lee et al 2002(Lee et al , 2004Zheng et al 2012;Shi et al 2013;Sun et al 2015;He et al 2016He et al , 2017aHe et al , 2017b. There are four possible causal mechanisms that we have summarized from existing studies.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the water level will rise in contraction zones and fall in regions of dilation (Wang and Manga 2010). Itaba et al (2008) computed that the sensitivity of the groundwater level to the crustal volumetric strain ranges from a few centimeters to 10 À8 strain. However, there is some evidence (Koizumi et al 2004;Wang and Manga 2010) that contradicts this hypothesis.…”
Section: Introductionmentioning
confidence: 99%